The Use of Mind Mapping Technique to Improve the EFL Students’ Reading Comprehension Ability of Darussalam Polytechnic - M. Bambang Purwanto; Marsinah Marsinah (Esteem Journal of English Education Study Programme, 2021)
Mind maps are visual frameworks such  as  figures, diagrams, or  charts used  to  present structural knowledge spatially with the intention of empowering comprehension and learning. Mind maps are effective in terms of helping communicate information because they can clarify complex concepts into simple, meaningful displays so that learners can develop a holistic understanding of the content to be learnt. Teachers may use mind mapping technique at  different  stages  of  instruction  for  example during  instruction  to  prepare  students to approach new  information and  clarify complex ideas, or  after instruction to  assess  and reinforce learning and instruction. This article reports on an investigation into the use of mind mapping technique whether it can improve reading comprehension ability and the students’ opinions towards the use of mind mapping technique. The research design used in this study was one-group pre test-post test design. The study employed both quantitative and qualitative data analyses from pre-and post-tests, a questionnaire, and an interview. The participants of the  study  were  35  first-year  students  enrolling  in  a  compulsory reading  course  called Communication and Reading Skills at Darussalam Polytechnic of Palembang.   Fifteen students (5 highly successful, 5 who did not show any improvement, and 5 unsuccessful) were selected for retrospective interviews. The results suggested that 1) The English reading comprehension post test mean score of students was higher than the pre test mean score at the 0.05 level of significance; 2) most students were satisfied with their own reading comprehension ability; 3) they enjoyed working in  group and  agreed that  mind  mapping technique was  a  useful technique and can be applied to non- English subjects. Findings and implications for further research are discussion.